The effect of experience, competence, independence, and professionalism of auditors on fraud detection - Lingga Sulistyowati; Supriyati Supriyati (Universitas Hayam Wuruk Perbanas, 2015)
This research aims to determine the effect of experience, competence, independence, and professionalism, as the independent variables, on fraud detection, as the depen-dent variable. The population of this research is the auditors who work for Public Accountant Firms in Surabaya. The sample used in this study consists of 58 audi-tors working in 12 Public Accounting Firms in Surabaya. Data are obtained through a survey of the questionnaires completed by senior accountants working in the Public Accounting Firm located in Surabaya City. The sampling technique is using purposive sampling method, and the research data are analyzed using mul-tiple regression analysis using SPSS version 20.00. The research results are ob-tained that the variables of experience, competence, and professionalism affect the fraud detection. But the variable of independence does not affect the fraud detection.